Twelve‑month rehospitalization after IBD‑related hospitalization in Germany: A retrospective cohort study using administrative hospital data - Christian Weigel; Sven H. Loosen; Kaneschka Yaqubi; Petra May; Tom Luedde; Christoph Roderburg; Karel Kostev (PLoS ONE, 2026)
Background/Aims Rehospitalization is an important indicator of disease burden and healthcare utilization in inflammatory bowel disease (IBD), yet real-world data from Germany remain scarce. This study aimed to describe 12‑month rehospitalization rates after IBD‑related inpatient treatment in Germany and to identify administrative and clinical factors recorded in hospital ICD‑10 coding that are associated with rehospitalization. Methods In this multicenter retrospective cohort study, anonymized administrative data from 49 German hospitals (Section 21 dataset, 2019–2023) were analyzed. Patients hospitalized with a primary diagnosis of Crohn’s disease (ICD-10 K50) or ulcerative colitis (ICD-10 K51) were included. The primary endpoint was any rehospitalization within 12 months after the index admission. Univariable and multivariable logistic regression models were used to determine factors of rehospitalization. Results A total of 3,202 patients were included (51.3% Crohn’s disease, 48.7% ulcerative colitis; mean age 44.2 years; 50.1% female). The 12-month rehospitalization rate was 22.6%, with a median time of 92 days (IQR 61–184). Independent factors in adjusted analyses were admission to a surgical department (AOR 1.79), peritoneal adhesions (AOR 1.98), type 2 diabetes mellitus (AOR 1.54), and hypokalemia (AOR 1.30). Age, sex, and IBD subtype showed no association. Conclusion Using administrative hospital data, we identified several ICD-10–coded comorbidities and treatment characteristics associated with higher rehospitalization rates. These findings highlight subgroups that may benefit from improved post-discharge management, although clinical interpretation is limited by the administrative nature of the dataset.